Two ends of the same thread: Reimagining the boundaries of personal and professional labour in eighteenth-century needlework and twenty-first-century crochet. Issue 1 (1st March 2021) - Banner, Jessica
As a researcher I have always maintained a firm boundary between my professional work and my personal hobbies. One of my most recent academic projects has traced the development of techniques and styles of needlework pictures and pictorial samplers made by young women in eighteenth-century England, while in my spare time I have increasingly turned to crocheting clothing and toys for friends and family. However, following recent developments in material culture and archival studies, which have encouraged reframing conceptions of authorship and resituating objects within larger networks of connection, it seems foolish to suppose that my work on needlework in the long eighteenth century is unaffected by my investment in crochet (and vice versa). This article aims to initiate discussions around the relationship between personal lives and professional research and seeks to explore how my practice of crochet and my research of textiles from the long eighteenth century are intimately connected.